9 things successful people do differently - Halvorson, Heidi Grant-, 1973- (Boston, Mass. : Harvard Business Press, 2012)
What you can learn from the world's most successful people - via research that uncovers the repeatable behaviors they use to reach their goals.
Get specific -- Seize the moment to act on your goals -- Know exactly how far you have left to go -- Be a realistic optimist -- Focus on getting better, rather than being good -- Have grit -- Build your willpower muscle -- Don't tempt fate -- Focus on what you will do, not what you won't do.
Includes bibliographical references (pages 93-101).
Online resource; title from PDF title page (EBSCO, viewed May 16, 2018).
Added to collection customer.56279.3
Keywords: Success; Success in business; Achievement motivation; Goal (Psychology); PSYCHOLOGY -- Applied Psychology; SELF-HELP -- Personal Growth -- General; SELF-HELP -- Personal Growth -- Happiness; SELF-HELP -- Personal Growth -- Success; Achievement motivation; Goal (Psychology); Success; Success in business; elektronické knihy; electronic books